Pathological Change and Whole Transcriptome Alternation Caused by ePTFE Implantation in Myocardium. (19th June 2021) - Shan, Yaping; Zhang, Wenbo; Chen, Gang; Shi, Qiqi; Mi, Yaping; Zhang, Huifeng; Jia, Bing
Abstract : Expanded polytetrafluoroethylene (ePTFE) is commonly used in cardiovascular surgery, but usually causes postoperation complications. Although great efforts have been done to relieve these complications or to understand their mechanism, there are no applicable strategies available and no understanding mechanisms, especially in the myocardium. Here, ePTFE membranes are implanted into the right ventricular outflow tract of rabbits, and the implant-related myocardium is dissected and analyzed by histology and transcriptome sequencing. ePTFE implantation causes myocardium inflammation and fibrosis. There are 1867 differently expressed mRNAs (DEmRNAs, 1107 upregulated and 760 downregulated) and 246 differently expressed lncRNAs (DElncRNAs, 110 upregulated and 136 downregulated) identified. Bioinformatic analysis indicates that the upregulated DEmRNAs and DElncRNAs are mainly involved in inflammatory, immune responses, and extracellular matrix remodeling, while the downregulated DEmRNAs and DElncRNAs are predominantly functioned in the metabolism and cardiac remodeling. Analysis of coexpression and regulatory relationship of DEmRNAs and DElncRNAs reveals that most DElncRNAs are trans -regulated on the relevant DEmRNAs. In conclusion, ePTFE implantation causes severe myocardial tissue damages and alters the transcriptome profiles of the myocardium. Such novel data may provide a landscape of mechanisms underlying the adverse reactions caused by ePTFE implantation and uncover new therapeutic targets for inhibiting the ePTFE-related complications.